The Relationship between Personality Profiles and the Esthetic Perception of Orthodontic Appliances - Selma Pascoal; Maria Gonçalves; Pietro Salvador; Rui Azevedo; Manuela Leite; Teresa Pinho (Hindawi Limited, 2024)
Introduction. In orthodontics, patients' esthetic expectations involve the final esthetic result as well as the treatment's appliance choice. Personality traits can influence patients' perception, treatment modality selection, expectations, compliance, and satisfaction with the treatment outcome, although there are very few studies on this interconnection between personality and orthodontic appliances. Objective. The aim of this study is to evaluate the relationship between personality traits and the esthetic perception of different orthodontic appliances. Materials and Methods. The online questionnaire is composed of three parts: (1) sociodemographic variables; (2) questions on the esthetic perception of different orthodontic appliances; (3) general personality assessment via the NEO-FFI. A total of 461 questionnaires were accepted. Results. There were statistically significant differences between laypeople and professionals related to assessing smiles and the need for orthodontic treatment. Laypeople identified a statistically significant relationship between personality traits and orthodontic appliances, in which esthetic perception is associated with high traits of agreeableness and openness. Neuroticism is most associated with orthodontic treatment with fixed appliances, which are the most conventional. Conclusions. Professionals tend to have a more critical judgment than laypeople as far as esthetics is concerned. Personality traits play an important role in esthetic perception and may influence orthodontic treatment.